A comprehensive review of cerebral oximetry in cardiac surgery. Issue 12 (24th November 2022) - Moore, Christina C.; Yu, Soojie; Aljure, Oscar
Abstract: Background: Patients who undergo cardiac surgery are at increased risk of stroke, postoperative cognitive decline, and delirium. These neurocognitive complications have led to increased costs, intensive care unit stays, morbidity, and mortality. As a result, there is a significant push to mitigate any neurological complications in cardiac surgery patients. Near‐infrared spectroscopy to measure regional cerebral oxygen saturations has gained consideration due to its noninvasive and user‐friendly nature. Cerebral oximetry desaturations during cardiac surgery have been linked to an array of adverse clinical outcomes. However, the most effective intraoperative interventions to protect this vulnerable patient population have yet to be ascertained. Aim of Study: To provide a comprehensive summary of the intraoperative management for cerebral oximetry desaturations during cardiac surgery. The review highlights clinical outcomes from cerebral oximetry use to quantify the importance of identifying cerebral desaturations during cardiac surgery. The review then interrogates possible interventions for cerebral oximetry desaturations in an effort to determine which interventions are most efficacious and to enlighten possible areas for further research. Methods: A narrative review of randomized controlled trials, observational studies, and systematic reviews with metanalyses was performed through August 2021. Results: There is significant heterogeneity among patient populations for which cerebral oximetry monitoring has been studied in cardiac surgery. Further, the definition of a clinically significant cerebral desaturation and the assessment of neurocognitive outcomes varied substantially across studies. As a result, metanalysis is challenging and few conclusions can be drawn. Cerebral oximetry use during cardiac surgery has not been associated with improvements in neurocognitive outcomes, morbidity, or mortality to date. The evidence to support a particular intervention for an acute desaturation is equivocal. Conclusions: Future research is needed to quantify a clinically significant cerebral desaturation and to determine which interventions for an acute desaturation effectively improve clinical outcomes.